Failed Implementation of Western Democracy in the Middle East - Nurislamia, Fika; Surwandono, Surwandono (Journal of Islamic World and Politics, 2023)
This article discusses how Peace Democratic Theory works as a foreign policy of the United States in spreading democracy around the world, especially in Islamic countries in the Middle East, and how the Islamic left criticizes the democratization process due to this foreign policy. Peace Democratic Theory ushers in Islamic Leftist Thought in assessing how the democratization process works out of conformity with Islamic Shari’a and the resulting chaos and prolonged conflict. The author brings a case study of the Iraq conflict due to the democratization process’s failure in this article. Using a descriptive qualitative approach, the author concluded that Peace Democratic Theory gave birth to democracy that established oligarchic politics. This article contributes information for various parties on the reasons for thinking about criticism between Islam and Peace Democratic Theory. In addition, this article is information material for multiple parties related to strategy in the conflict between Islam and Peace Democratic Theory.